Antibacterial Activity of Plumeria alba L. Leaf Ethanol Extract Against Propionibacterium acnes - Komala, Oom; Srinarayani, Kadek; Utami, Novi Fajar (Jurnal ILMU DASAR, 2024)
The Plumeria alba L. leaves are empirical as an alternative to treatment as an antibacterial to Propionibacterium acnes, Staphylococcus aureus and Salmonella typhi, as aromatherapy for the repellant and the denture cleanser of the growth of the Candida albicans in the synthetic nylon base. It has been known to contain alkaloids, flavonoids, saponin, tannin, and fenol that have activity as antibacterial. The study aims to determine the antibacterial activity and to identify the best concentration of 70% ethanol extract of P. alba L. leaf to P. acnes. The method used in extraction is a maceration with 70% ethanol solvent which is concentrated using a rotary evaporator. Extract of ethanol 70% of P. alba L. leaves was used to determine antibacterial activity by determining the Minimum Inhibitory Concentration (MIC) using solid dilution and the width of inhibition area by diffusion method of paper discs at concentrations of 30%, 40%, and 50%. Phytochemical tests were carried out of alkaloid, flavonoid, saponin, tannin and fenol qualitatively. The result showed that ethanol 70% extract of P. alba L. leaf had antibacterial activity against P. acnes with MIC at 25% concentration. The best antibacterial activity from ethanol extract 70% of P. alba L. leaves at a concentration of 50% with inhibitory, namely 9.4 mm. The P. alba L. leaves phytochemical test contains alkaloids, flavonoids, saponins, tannins, and fenol. The conclusion ethanol extract 70% of P. alba L. leaves have the antibacterial activity against P. acnes.